2020
DOI: 10.1111/1365-2745.13419
|View full text |Cite
|
Sign up to set email alerts
|

Restoring functionally diverse communities enhances invasion resistance in a freshwater wetland

Abstract: 1. Understanding how plant communities reassemble is particularly relevant when invaders are part of the species pool and can compromise restoration or conservation goals. If initial species composition has a lasting impact on community dynamics, it may be possible to enhance biotic resistance to invasion, particularly through diversity effects, by manipulating early community composition. Diversity effects have been investigated much less in wetlands than in uplands. 2. We conducted a large plant community re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 96 publications
4
21
0
Order By: Relevance
“…In other words, it is not just proximity to intact native stands that drives recovery (as found by Rohal, Cranney, & Kettenring, 2019), but also the quality and diversity of the surrounding areas that are important. Given the importance of restoring diverse native vegetation for future invasion resistance to Phragmites (Byun et al, 2013; Byun, de Blois, et al, 2020), it is essential to restore wetlands in watersheds where the vegetation in the larger landscape is of sufficient quality and diversity to facilitate rapid recovery. Where this approach is infeasible, it is important to recognize that landscape conditions will constrain what is possible in a restoration site (Matthews, Peralta, et al, 2009) and that greater financial investment is required including to augment recovery by reintroducing appropriate native species.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is not just proximity to intact native stands that drives recovery (as found by Rohal, Cranney, & Kettenring, 2019), but also the quality and diversity of the surrounding areas that are important. Given the importance of restoring diverse native vegetation for future invasion resistance to Phragmites (Byun et al, 2013; Byun, de Blois, et al, 2020), it is essential to restore wetlands in watersheds where the vegetation in the larger landscape is of sufficient quality and diversity to facilitate rapid recovery. Where this approach is infeasible, it is important to recognize that landscape conditions will constrain what is possible in a restoration site (Matthews, Peralta, et al, 2009) and that greater financial investment is required including to augment recovery by reintroducing appropriate native species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have found that uninvaded native communities have higher functional diversity than invaded communities, which was interpreted as evidence of invasive species decreasing functional diversity through competitive displacement (Jucker et al, 2013;Michelan et al, 2010). Of the few invasion studies to manipulate functional diversity experimentally, two found that invader performance decreased in more functionally diverse native communities, providing support for the biotic resistance hypothesis (Byun et al, 2020;Feng et al, 2019). However, another experiment found that colonizers were more successful in more functionally diverse plots and attributed this to unoccupied niche space increasing with functional diversity (Galland et al, 2019).…”
Section: The Absence Of a Relationship Between Multivariate Functional Diversity And Invasionmentioning
confidence: 92%
“…The richness of native species was negatively correlated with A. artemisiifolia seed yield, regardless of herbicide treatment. It is likely that plant species in more diverse communities occupy a wider range of ecological niches and are more apt to compete with A. artemisiifolia ( Byun et al, 2013 , 2020 ). Diversified interspecific competition largely reduces the fitness of A. artemisiifolia , thereby providing a solid basis for effective weed control using herbicides at low doses prior to A. artemisiifolia outbreaks.…”
Section: Discussionmentioning
confidence: 99%